Large-scale controls on potential respiration and denitrification in riverine floodplains - Welti, Nina (Diverse TCRs recognize murine CD1, 2012)
Restoration measures of deteriorated river ecosystems generally aim at increasing the spatial heterogeneity and connectivity of these systems in order to increase biodiversity and ecosystem stability. While this is believed to benefit overall ecological integrity, consequences of such restoration projects on biogeochemical processes per se (i.e. ecosystem functioning) in fluvial systems are rarely considered. We address these issues by evaluating the characteristics of surface water connection between side arms and the main river channel in a former braided river section and the role and degree of connectivity (i.e. duration of surface water connection) on the sediment biogeochemistry. We hypothesized that potential respiration and denitrification would be controlled by the degree of hydrological connectivity, which was increased after floodplain restoration. We measured potential microbial respiration (SIR) and denitrification (DEA) and compared a degraded floodplain section of the Danube River with a reconnected and restored floodplain in the same river section. Re-establishing surface water connection altered the controls on sediment microbial respiration and denitrification ultimately impacting potential microbial activities. Meta-variables were created to characterize the effects of hydrology, morphology, and the available carbon and nutrient pools on potential microbial processing. Mantel statistics and path analysis were performed and demonstrate a hierarchy where the effects of hydrology on the available substrates and microbial processing are mediated by the morphology of the floodplain. In addition, these processes are highest in the least connected sites. Surface water connection, mediated by morphology regulates the potential denitrification rate and the ratio of N2O to N2 emissions, demonstrating the effects of restoration in floodplain systems